Epiphytic Weeds Control by Root Infusion Method in Oil Palm - Edyson, Edyson; Murgianto, Fitrah; Ardiyanto, Adhy (Department of Agrotechnology, Universitas Muhammadiyah Yogyakarta, 2022)
Epiphytic weeds living on oil palm trunks will complicate harvesting activities. In addition, the presence of this weed can increase the risk of accidents being hit by fruit during harvesting. The objective of this research was to obtain herbicide and its efficient concentrations to control epiphytic weeds using root infusion method. The research was arranged in a single factor completely randomized design (CRD) with five treatments and five replications. Active ingredients of herbicide that used were methyl metsulfuron at a concentration of 20%, 30%, and 40%, glyphosate 30%, and triclopyr + diesel fuel at a ratio of 1:19. All treatments except triclopyr were diluted in 100 ml water for each epiphytic weed. Weed mortality rate (%) was observed every week for one month. The results showed that a solution of 30% methyl metsulfuron herbicide in 100 ml of water and 30% glyphosate in 100 ml of water was the most optimal treatment in controlling epiphytic weeds. Cutting the entire suction root of epiphytic weeds can increase the chance of weed mortality.